Internet of Things and Blockchain-Based Framework for Coronavirus (COVID-19) Disease - Alam, Tanweer; Mohamed Benaida, (International Journal of Online and Biomedical Engineering (iJOE), 2022)
The COVID-19 is a highly contagious infection which is already had a catastrophic effect on the most serious diseases, including death, around the world. Blockchain-based healthcare systems are being introduced to help simplify mobile and telehealth services, reducing patient stress and the cost of critical clinical services. shared the advantages of blockchain for building a cutting-edge authentication infrastructure and detecting COVID-19 suspicious cases. The authors presented a blockchain-based design for developing a real-time cellular health monitoring system for COVID-19 patients in this paper. This study identifies clinical problems and electronic diagnoses for people with COVID-19 infectious diseases and provides a framework for them. Any mobile application can be configured on digital devices such as smartphones. COVID-19 patients may benefit from such applications. Smartphone apps are designed to save time and money while increasing the efficiency of infectious patients. IoT and Blockchain strategies are presented in the four-layer structure.